Herbicide efficacy for aquatic Alternanthera philoxeroides management in an early stage of invasion: integrating above‐ground biomass, below‐ground biomass and viable stem fragmentation. (6th July 2017) - Clements, D; Dugdale, T M; Butler, K L; Florentine, S K; Sillitoe, J
Summary: Alternanthera philoxeroides is a problematic invasive plant in many regions of the world that is difficult to control once naturalised. It poses a threat to agricultural productivity, biodiversity and social amenity values of aquatic environments. Significant research has been conducted internationally, regarding the efficacy of different herbicides for control of A. philoxeroides . However, no studies have looked at key aspects of control for effective management in an early stage of invasion of aquatic environments, hindering eradication and control programmes. This study evaluates the efficacy of herbicides and surfactants on key A. philoxeroides response metrics, including control of above‐ground biomass, below‐ground biomass and production of viable stem fragments. This study concluded that glyphosate (isopropylamine salt) minimises viable stem fragment production post‐herbicide application, compared with imazapyr and metsulfuron, thus reducing the potential for dispersal throughout catchments and waterways. In contrast, imazapyr and metsulfuron provided more effective control than glyphosate for A. philoxeroides growing on exposed embankments. We propose that an effective management strategy for early invasion of aquatic A. philoxeroides, using herbicides, would be to conduct initial applications of glyphosate to control overwater biomass and limit dispersal of viable stem fragments. Once infestations have been forced back to the embankment, imazapyr or metsulfuron treatments will provide longer term control.